Pattern of Clinical Medication Seeking for Import Malaria by Migrant Workers - Muhammad Mahmudi; Ririh Yudhastuti (Universitas Airlangga, 2015)
Trenggalek District in 2014 found 83 out of 89 cases of malaria were imported malaria cases carried by migrant workers. The case involved two domiciles that affected the search for treatment. This study aims to provide an overview of the search patterns for imported clinical malaria treatment for migrant workers who come from the area in the Public health center (PHC) of Pandean, Trenggalek District. This type of research is cross-sectional descriptive. Data were collected through interviews with 26 respondents of imported malaria patients who have a history of migrant work in 2013-2015 that were selected purposively. Interviews were conducted to obtain data on the characteristics of the respondents, where they experienced pain when to seek treatment first, place of treatment first, place of diagnosis first, treatment follow-up, and recovery. The results showed that all respondents were male, the majority aged 20-30 years (53.8%), working outside the island as migrant wood care workers (50%), suffering more first pain in the migration destination (53, 8%), the most treatment was on the 3rd day after suffering from symptoms (34.6%). Respondents who experienced illness in the PHC of Pandean area received the most first treatment at the PHC (42.3%) and at the Hospital (19.2%) for the migration destination. The clinical diagnosis of malaria was obtained at the PHC was 69%, but only 11.5% received a post-treatment follow-up visit and another 19.2% did not recover or experience a relapse. Most respondents chose the most advanced treatment at the PHC. All respondents chose clinical treatment as the first place of treatment. Need to be followed up after ongoing treatment.